2008
DOI: 10.1016/j.bbmt.2007.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab for the Treatment of Steroid-Refractory Acute Graft-Versus-Host Disease

Abstract: The treatment of steroid-refractory acute graft-versus-host disease (aGVHD) remains a clinical challenge, for which no standard therapy exists. Alemtuzumab is a humanized anti-CD52 monoclonal antibody (mAb) that has been successfully used as part of conditioning regimens for hematopoietic stem cell transplantation (HSCT) to prevent GVHD. The purpose of this study was to evaluate the safety and efficacy of alemtuzumab in treating steroid-refractory aGVHD (>or=grade II) following HSCT. Eighteen patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…The colleagues from Houston have reported effectiveness of subcutaneous alemtuzumab in acute as well as chronic GVHD. 11,12 In conclusion, in this difficult to treat patient population, low doses of alemtuzumab applied every 2 weeks may lead to relevant GVHD responses with a more favourable benefit-risk ratio. This schedule should be evaluated in a prospective randomized trial.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The colleagues from Houston have reported effectiveness of subcutaneous alemtuzumab in acute as well as chronic GVHD. 11,12 In conclusion, in this difficult to treat patient population, low doses of alemtuzumab applied every 2 weeks may lead to relevant GVHD responses with a more favourable benefit-risk ratio. This schedule should be evaluated in a prospective randomized trial.…”
Section: Discussionmentioning
confidence: 95%
“…Licensed for the treatment of fludarabine-refractory B-cell CLL, 2 alemtuzumab was also used in T-cell tumors [3][4][5] and due to its known immunosuppressive activity in autoimmune diseases 6 and for GVHD prevention. 7,8 Although alemtuzumab in the treatment of acute and chronic GVHD in small studies and case reports has already shown therapeutic responses, [9][10][11][12][13] very recently Schnitzler et al 14 reported 20 patients with severe intestinal acute GVHD treated successfully with alemtuzumab. Here, we show the efficacy of alemtuzumab for intestinal and liver grade III and IV acute GVHD in 18 steroid-refractory patients and support the idea that smaller doses may be preferable.…”
Section: Introductionmentioning
confidence: 99%
“…On day 28 of treatment 15 patients had responses and 10 out of the 15 patients were alive at 11 months. Fourteen patients developed infections including 11 who developed CMV reactivation [90]. In another phase II trial of 10 patients with grade III and IV aGVHD, 5 responded to treatment but all 10 died with a median period of 40 days [91].…”
Section: Alemtuzumab (Campath)mentioning
confidence: 99%
“…[1][2][3][4][5] Although several different agents have been proposed as therapy for steroid-refractory aGVHD, there remains no consensus as to optimal management following failure of corticosteroids. At our institution, steroid-refractory aGVHD is routinely treated with antithymocyte globulin (ATG), etanercept ± mycophenolate mofetil.…”
mentioning
confidence: 99%
“…5 Although this approach is able to salvage a significant proportion of patients, prognosis is historically dismal in those patients refractory to second-line therapy. Given the reports of steroid-refractory aGVHD responding to alemtuzumab, [1][2][3][4]6,7 we have incorporated this agent as third-line therapy in patients failing the above strategies. Herein, we report the outcome of 13 patients with steroid and ATG/etanercept-refractory aGVHD treated with alemtuzumab as third-line therapy at our institution.…”
mentioning
confidence: 99%